How do you solve 2x ^ { 2} + 10x + 52= ( x + 7) ^ { 2}?

2 Answers
May 22, 2018

x = 1, x =3

Explanation:

2x ^ { 2} + 10x + 52= ( x + 7) ^ { 2}

FOIL the right side:

2x^2+10x+52 = (x+7)(x+7)

2x^2+10x+52 = x^2 +14x +49

Move the terms to one side of the equation:

2x^2+10x+52 - x^2-14x -49= 0

combine like terms:

x^2 -4x +3 =0

factor:

(x-1)(x-3) = 0

solutions (roots):

x = 1, x =3

May 22, 2018

"FOIL" terms on the right and subtract terms from both sides. Use quadratic formula to obtain answers.

Explanation:

2x^2+10x+52=(x+7)^2

2x^2+10x+52=(x+7)(x+7)

Foil the terms on the right (First, Outsides, Insides, Last).

2x^2+10x+52=x^2+7x+7x+49

2x^2+10x+52=x^2+14x+49

x^2+10x+52=14x+49

x^2+52=4x+49

x^2+3=4x

At this point, it may be obvious that one answer is x=1. The second answer may not be as obvious.

If not, we can always apply the Quadratic Formula, where x^2-4x+3=0.

(4+sqrt(16-4*1*3))/(2*1) or (4-sqrt(16-4*1*3))/(2*1)

6/2=3 or 2/2=1.

x=3 or x=1